EVALUASI MODEL DATA WAREHOUSE UNTUK MENDUKUNG MANAJEMEN PENDIDIKAN DENGAN TAM - Raissa Amanda Putri; Sriani Sriani (Universitas Islam Negeri Sumatera Utara, 2018)
User acceptance is important in the software development process. The purpose of this paper is to evaluate a data warehouse model that can display all useful information that can support education management. The design results of this model will be evaluated using the Technology Acceptance Model (TAM) which describes the acceptance of information technology with certain dimensions that may affect the acceptance or not of information technology by the user. Methods of data collection using questionnaires distribution techniques, interviews and observation. The result of this research is evaluation of data warehouse model to support education management.Keywords: Model Evaluation, Data Warehouse, Education Management, Technology Acceptance Model